MiR‐152 reduces human umbilical vein endothelial cell proliferation and migration by targeting ADAM17. Issue 12 (8th May 2014) - Wu, Yang; Huang, Aixue; Li, Tao; Su, Xueting; Ding, Hongmei; Li, Hui; Qin, Xingliang; Hou, Lubin; Zhao, Qiang; Ge, Xingfeng; Fang, Tao; Wang, Rong; et al.
Abstract : As a cleavage enzyme of precursor TNF‐α, the high expression level of ADAM17 in endothelial cells is an important factor in atherosclerosis. In this study, we demonstrate that ADAM17 is the target of miR‐152. We found that miR‐152 could reduce TNF precursor cleavage and inhibit cell proliferation and migration by targeting ADAM17 in human umbilical vein endothelial cells (HUVECs). Furthermore, the expression pattern of miR‐152 and corresponding target ADAM17 was opposite in HUVECs under hypoxic conditions. The levels of circulating miR‐152 in AS patient sera were lower than those detected in the sera of normal individuals. Our results indicate that miR‐152 may be involved in the development of human atherosclerosis and could be used as diagnostic biomarker or therapeutic target in atherosclerosis. Abstract : ADAM17 is an important factor in inflammation‐associated vascular diseases. ADAM17 is a direct target gene of miR‐152. MiR‐152 inhibits the proliferation and migration of HUVECs. Serum miR‐152 levels are much lower in atherosclerosis patients than in normal individuals. MiR‐152 could be used as a diagnostic biomarker or therapeutic target in atherosclerosis.